Nightmares and psychiatric symptoms: a systematic review of longitudinal, experimental, and clinical trial studies - Sheaves, B; Rek, S; Freeman, D (Elsevier, 2022)
Nightmares occur across a wide range of psychiatric disorders, but outside of PTSD presentations are infrequently considered a treatment priority. We aimed to assess evidence for a contributory causal role of nightmares to the occurrence of psychiatric disorders, and vice versa. A systematic review was conducted of longitudinal, experimental, and clinical trial studies. Twenty-four longitudinal, sixteen trials, and no experimental studies were identified. Methodological shortcomings were common, especially the use of single-item nightmare assessment. Thirty-five studies assessed the path from nightmares to psychiatric symptoms. Depression (n = 10 studies), PTSD (n = 10) and anxiety (n = 5) were the most commonly assessed outcomes in trials. Most were not designed to assess the effect of nightmare treatment on psychiatric symptoms. Treating nightmares led to moderate reductions in PTSD and depression, small to moderate reductions in anxiety, and potentially moderate reductions in paranoia. Nightmares increased the risk of later suicide outcomes (n = 10), but two small pilot trials indicated that treating nightmares might potentially prevent recovery of suicidal ideation. PTSD treatment led to large reductions in trauma-related nightmares (n = 3). The limited literature suggests that treating nightmares may be one route to lessening threat-based disorders in particular, suggestive of a causal relationship. Overall, however, nightmares in most disorders are greatly understudied.